GEOGRAPHICAL FEATURES OF PILGRIMAGE TOURISM IN KASHKADARYA REGION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article talks about the importance of Kashkadarya region in the development of pilgrimage tourism. The author, relying on archaeological data, archival documents and written sources, analyzed the problem on the basis of available scientific and historical literature and studied the features of the Kashkadarya region in the development of tourism. In addition, the article provides information about the activities of our research government in the field of tourism.